2020
DOI: 10.1016/j.iref.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

125 ​Years of time-varying effects of fiscal policy on financial markets

Abstract: This paper examines the effect of fiscal policy on financial markets over a long span of 125 years. Unlike existing studies that mainly focus on monetary policy shocks and model-based identification of fiscal policy shocks, we use a time-varying parameter model to study the effect of fiscal policy with much cleaner and direct identification of fiscal policy shocks. In addition, we extend our analysis by measuring the response volatility in these markets and separately study the effects of good and bad componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…The decrease of interest rates for the first and the second period is smaller in size for the model with changing coefficients, than the model with constant parameters. Moreover, a supply shock has a positive effect on stock volatility -a result in line with theory, i.e., higher economic activity leads to more trading and higher volatility (Marfatia et al, 2020). The bands of the shock are narrower for the first two In Figure 3, we depict the cumulative IRFs for a one standard deviation positive shock to SSR growth rates.…”
Section: Main Analysis Resultssupporting
confidence: 73%
“…The decrease of interest rates for the first and the second period is smaller in size for the model with changing coefficients, than the model with constant parameters. Moreover, a supply shock has a positive effect on stock volatility -a result in line with theory, i.e., higher economic activity leads to more trading and higher volatility (Marfatia et al, 2020). The bands of the shock are narrower for the first two In Figure 3, we depict the cumulative IRFs for a one standard deviation positive shock to SSR growth rates.…”
Section: Main Analysis Resultssupporting
confidence: 73%
“…As part of future research, it would be interesting to extend our analysis to emerging equity markets and provide a comparative analysis. Moreover, with some studies having analyzed the impact of fiscal policy shocks on stock market in the wake of the ZLB (see Marfatia et al, (2020) for a detailed literature review), an extension of our work would be to investigate the impact of fiscal policy shocks contingent on levels of sentiment.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested that the development of these two sectors of the financial system each has a statistically significant effect on economic growth in emerging and developing economies such as SSA. (Marcelin and Mathur, 2016;Sepehrdoust & Shabkhaneh, 2018;Dumičić, 2019;Marfatia et al, 2020). Consistent with these findings, developing countries have tended to focusing on modernizing and liberalizing their financial systems to allow for greater private sector participation (Fowowe, 2013;Shijaku and Kalluci, 2013; .…”
Section: Introductionmentioning
confidence: 91%